Computational Design of Mn4 Molecules with Strong Intramolecular Exchange Coupling - Tuan, Nguyen Anh; Thanh, Nguyen Van; Nu, Tran Thi Thuy; Sinh, Nguyen Huy; Khai, Vu Van; Chi, Dam Hieu; Katayama, Shin-ichi (Communications in Physics, 2011)
The geometric and electronic structures of [Mn44+Mn3+3(µ3-L2 -)3(µ3-X -(OAc) - 3(dbm) -3] (L = O, X = F, dbmH = dibenzoyl-methane) molecule has been studied by first-principles calculations. It was shown in our previous paper that the ferrimagnetic structure of Mn^4 + Mn^3 + _3 molecules is determined by the π type hybridization between the d_z^2 orbitals at the three high-spin Mn^3 + ions and the t_2g orbitals at the Mn^4 + ion by the p orbitals at the μ _3-L^2 - ions. To design new Mn^4 + Mn^3 + _3 molecules having much more stable ferrimagnetic state, one approach is suggested. That is controlling the Mn^4 + -(μ _3-L^2 - )-Mn^3 + exchange pathways by rational variation in μ _3-L ligands to strengthen the hybridization between Mn ions. By this ligand variation, J_AB can be enhanced by a factor of 3. Our results should facilitate the rational synthesis of new single-molecule magnets.